Hospital acquired Clostridioides difficile infection and risk factors for severity in a university hospital: A prospective study - TİGEN, ELİF; BİLGİN, HÜSEYİN; ÜLGER, NURVER; KORTEN, VOLKAN (MOSBY-ELSEVIER, 2020)
Background: Clostridioides difficile infection (CDI) is a well-known cause of health care-associated diarrhea. Data about CDI epidemiology of Turkey is limited. This study investigates CDI incidence, clinical characteristics, and factors associated with severe CDI in a tertiary care center university hospital. Methods: This is a case control study was conducted between 2012 and 2016. We included all patients, 18 years of age or more, with CDI diagnosis. For each patient diagnosed with CDI, information was collected concerning the severity of disease, treatment regimen, treatment response, disease recurrence, 30-day case fatality. Cases defined as severe hospital acquired CDI (HA-CDI) and controls defined as non-severe CDI patients. Results: We identified 100 cases of HA-CDI out of 111 patients. Total CDI incidence was 1.19/10,000 patient days. The incidence decreased 32.5% during the study period. We identified severe CDI in 24% of patients. Age and admission to intensive care unit were independent risk factors for severe CDI. Conclusion: This study reports a 5-year prospective epidemiology of CDI in a tertiary care center in Istanbul, Turkey. The findings of this study suggest that HA-CDI incidence and proportion of severe CDI is low compared to European and US literature. We believe that CDI is underreported, neglected but still an important health care associated infection in Turkey. (C) 2020 Association for Professionals in Infection Control and Epidemiology, Inc. Published by Elsevier Inc. All rights reserved.
Keywords: Clostridioides difficile; Severe Clostridioides difficile infection; Epidemiology; Turkey; CLINICAL-FEATURES; BINARY TOXIN; DIARRHEA; EPIDEMIOLOGY; STRAINS; SOCIETY; EUROPE